Cover Feature: Isomerization Dynamics of Electronically Coupled but Thermodynamically Decoupled Bisazobenzenes (ChemPhotoChem 6/2019). Issue 6 (5th June 2019) - Boumrifak, Chokri; Yang, Chong; Bellotto, Silvia; Wegner, Hermann A.; Wachtveitl, Josef; Dreuw, Andreas; Slavov, Chavdar
Abstract : The Cover Feature illustrates the splitting of the isomerization pathways after selective excitation of a molecular double‐photoswitch. Photoresponsive structures composed of multiple photoswitchable units offer the possibility of more diverse and complex control applications. For example, o‐bisazobenzenes show unusual electronic coupling affecting the properties of the individual azobenzene units. Time‐resolved spectroscopic experiments supported by quantum chemical calculations revealed that electronic coupling removes the bias introduced by selective excitation of one azobenzene moiety. More information can be found in the Article by C. Boumrifak et al. on page 411 in Issue 6, 2019 (DOI: 10.1002/cptc.201900077 ).